Livelihood resilience and livelihood construction path of China's rural reservoir resettled households in the energy transition - Chen, Shaojun; Wu, Jing; Zhou, Kexin; Li, Ru (Frontiers in Sustainable Food Systems, 2023)
The construction of reservoirs has led to difficult livelihood transitions of resettled households after relocation and resettlement, resulting in a series of socioeconomic problems. How to scientifically integrate regional resource advantages and improve the livelihood resilience of resettled households has become an important problem to be solved to prevent and resolve social equity and justice risks and sustainable livelihood development. Taking Xiangjiaba Hydropower Station (Yunnan Reservoir area) as an example, the evaluation index system was constructed from the three dimensions of buffer capacity, self-organization capacity and learning capacity, the gray correlation degree method was used to evaluate index system, and the clustering method was selected to screen the indices that have a great impact on livelihood resilience. On this basis, the comprehensive index method was used to calculate the livelihood resilience, and the contribution degree model was used to identify the main contribution factors of livelihood resilience and to explore the path of livelihood construction to improve the livelihood resilience of resettled households. The results showed that (1) the level of livelihood resilience of resettled households was not high as a whole, in which the self-organization capacity was the strongest, the buffer capacity was the second strongest, and the learning capacity was the weakest; (2) there were differences in the livelihood resilience of resettled households who choose different livelihood modes. Among them, buffer capacity, learning capacity and livelihood resilience were characterized by wage operation type > part-time balanced type > agricultural operation type > subsidy dependent type, while self-organization capacity was characterized by agricultural operation type > part-time balanced type > wage operation type > subsidy dependent type. (3) The main contribution factors of the livelihood resilience of resettled households who choose different livelihood modes are similar. The number of laborers, participation in social organizations, skills training opportunities and 11 other main indices promote the formation and development of livelihood resilience from different dimensions. (4) The livelihood of resettled households should follow the construction path of “identifying transition capacity, clarifying resource advantages, strengthening livelihood support, and promoting livelihood reorganization” to promote the comprehensive improvement of livelihood resilience, ultimately achieving sustainable livelihood and high-level welfare. The livelihood resilience of resettled households is a continuous and dynamic development process, therefore, it is necessary to further improve the dynamic monitoring and evolution process of livelihood resilience, incorporate the impact of diverse data. This is also an important breakthrough in the study of livelihood resilience.